Sustainability: A Regional Australian Experience of Educating Secondary Geography Teachers - Michael Danaher; Jiaping Wu; Michael Hewson (Education Sciences, 2021)
The United Nations Sustainable Development Goal (SDG) number four seeks an equitable and widespread education that enables an outcome of sustainable development by 2030. Intersecting the studies of society and earth processes, a geographical education is well placed to make cohesive sense of all the individual knowledge silos that contribute to achieving sustainability. Geography education is compulsory for the first three years of the secondary education curriculum in Australia; however, research has shown that many geography teachers are underprepared and report limitations in their teaching of sustainability. This article engages with this research problem to provide a critical reflection, using experiential knowledge as an analytical lens, on how tertiary level geography training at one Australian regional university can equip undergraduate teacher education students with the values, knowledge, and skills needed to develop their future students’ understanding and appreciation of the principles of sustainability. The authors unpacked a geography minor for a Bachelor of Secondary Education degree at Central Queensland University and, deploying content analysis, explain how three units in that minor can develop these students’ values, knowledge, and skills through fostering initiatives and activities. The analysis was framed by elements of pedagogy that offer learners a context for developing active, global citizenship and participation to understand the interdependencies of ecological, societal, and economic systems including a multisided view of sustainability and sustainable development. The study concluded that the three geography units engage student teachers in sustainable thinking in a variety of ways, which can have a wider application in the geography curricula in other teacher education courses. More importantly, however, the study found that there is a critical need for collaboration between university teachers of sustainability content and university teachers of school-based pedagogy in order to maximise the efficacy of sustainability education in schools.